Secretome Analysis of Hypoxia‐Induced 3T3‐L1 Adipocytes Uncovers Novel Proteins Potentially Involved in Obesity. Issue 7 (29th March 2018) - Laria, Anna Elisa; Messineo, Sebastiano; Arcidiacono, Biagio; Varano, Mariaconcetta; Chiefari, Eusebio; Semple, Robert K.; Rocha, Nuno; Russo, Diego; Cuda, Giovanni; Gaspari, Marco; Brunetti, Antonio; Foti, Daniela P.
Abstract: In the obese state, as adipose tissue expands, adipocytes become hypoxic and dysfunctional, leading to changes in the pattern of adipocyte‐secreted proteins. To better understand the role of hypoxia in the mechanisms linked to obesity, we comparatively analyzed the secretome of murine differentiated 3T3‐L1 adipocytes exposed to normoxia or hypoxia for 24 h. Proteins secreted into the culture media were precipitated by trichloroacetic acid and then digested with trypsin. The peptides were labeled with dimethyl labeling and analyzed by reversed phase nanoscale liquid chromatography coupled to a quadrupole Orbitrap mass spectrometer. From a total of 1508 identified proteins, 109 were differentially regulated, of which 108 were genuinely secreted. Factors significantly downregulated in hypoxic conditions included adiponectin, a known adipokine implicated in metabolic processes, as well as thrombospondin‐1 and ‐2, and matrix metalloproteinase‐11, all multifunctional proteins involved in extracellular matrix (ECM) homeostasis. Findings were validated by Western blot analysis. Expression studies of the relative genes were performed in parallel experiments in vitro, in differentiated 3T3‐L1 adipocytes, and in vivo, in fat tissues from obese versus lean mice. Our observations are compatible with the concept that hypoxia may be an early trigger for both adipose cell dysfunction and ECM remodeling.